2002
DOI: 10.2175/106143002x139794
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant Export from Various Land Uses in the Upper Neuse River Basin

Abstract: Because of the relatively high variability of pollutant export from urban land uses, a significant number of monitoring studies, including data from many storms, are needed to adequately characterize export from urban land uses. Pollutant runoff from six small drainage areas with different land uses was monitored for at least 20 storm events over the course of more than 1 year. The land uses included singlefamily residential, golf course, industrial, dairy cow pasture, construction site, and wooded site. Avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 11 publications
1
67
1
Order By: Relevance
“…Forest and cultivated croplands decreased ϳ7.28 ϫ 10 3 km 2 over the past decade, giving way to land development (USDA 2001;Line et al 2002; National Agricultural Statistics Service 2004). The watershed also contains ϳ1.75 ϫ 10 6 swine (ϳ3.5ϫ10 6 swine produced per year, or 18% of the state's annual total, mostly in concentrated animal feed operations or CAFOs), contributing an equivalent in sewage of about 7 million people (American Society of Agricultural Engineers 1998), and ϳ4.8 ϫ 10 7 poultry produced per year (USDA 2001; Table 1).…”
Section: Study Areamentioning
confidence: 99%
“…Forest and cultivated croplands decreased ϳ7.28 ϫ 10 3 km 2 over the past decade, giving way to land development (USDA 2001;Line et al 2002; National Agricultural Statistics Service 2004). The watershed also contains ϳ1.75 ϫ 10 6 swine (ϳ3.5ϫ10 6 swine produced per year, or 18% of the state's annual total, mostly in concentrated animal feed operations or CAFOs), contributing an equivalent in sewage of about 7 million people (American Society of Agricultural Engineers 1998), and ϳ4.8 ϫ 10 7 poultry produced per year (USDA 2001; Table 1).…”
Section: Study Areamentioning
confidence: 99%
“…Nutrients (nitrogen and phosphorus) are problematic pollutants in urban stormwater runoff (Bannerman et al 1993;Line et al 2002). Likewise, in agricultural areas, rainfall-driven runoff of phosphorus into streams is problematic (Edwards and Daniel 1992) and occurs both from the erosion of particulate phosphorus and surface or subsurface movement of dissolved phosphorus (Sims et al 1998;Nash and Halliwell 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, field studies have found low concentrations of nitrate in storm run-off from fertilized lawns (Petrovic, 1990;Garn, 2002), with the exception of storm events after fertilizer applications (Kelling & Peterson, 1975). For example, Line et al (2002), working in suburban sites in North Carolina, measured nitrogen concentrations to be four times higher in run-off from single family residential land uses during February compared to fall or winter concentrations. Seasonal variability has also been observed for soil water nitrate concentrations from fertilized lawns.…”
Section: Introductionmentioning
confidence: 99%